Graphitic carbon nitride-graphene hybrid nanostructure as a catalyst support for polymer electrolyte membrane fuel cells - Mansor,N; Jia,J; Miller,TS; Suter,T; Jorge,AB; Gibbs,C; Shearing,P; McMillan,PF; Mattevi,C; Shaffer,M; Brett,DJL (ECS Transactions, 2016)
Graphitic carbon nitrides form a class of semiconducting graphene-like polymeric materials with visible light absorption and photocatalytic properties. In addition to high nitrogen content and tunable structure, it was shown that graphitic carbon nitride based on polytrazine imide (PTI) sheets exhibit excellent anti-corrosion ability in ex-situ fuel cell environments. However, in bulk form, their low surface area and poor conductivity limits their applications in fuel cells. In this work, PTI was exfoliated to form an ink made from single to few-layer nanosheets. The ink was then processed to produce 3D networks of carbon nitride nanosheets/reduced graphene oxide (PTI-rGO) hybrid aerogel with large interconnecting pores for fast mass transport of reactants and high surface area. The material was decorated with platinum nanoparticles, and then investigated for its electrochemical properties and applications as a catalyst support for polymer electrolyte membrane (PEM) fuel cells. Initial results show that the cathode catalytic activity of Pt/rGO-PTI hybrid is significantly improved in comparison to Pt/PTI or Pt/rGO. In addition, the in-situ fuel cell performance of Pt/PTI as anode catalyst is comparable to commercial Pt/C especially at low densities, making it attractive as an alternative, durable anode catalyst support material to conventional carbon black.